1998
DOI: 10.1007/s002400050043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary IL-1α and IL-1β in gravid females and patients with bacterial cystitis and microscopic hematuria

Abstract: Significant elevations of IL-1alpha and IL-1beta occur in patients with bacterial cystitis and microscopic hematuria. Correlation between pyuria and cytokine elevation was stronger for IL-1beta than for IL-1alpha. Changes in IL-1alpha may reflect changes in the bladder epithelium rather than in the inflammatory leukocytes. The ability of IL-1alpha and IL-1beta to serve as markers for bacterial cystitis in gravid females is diminished due to high basal levels during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Increased serum levels of IL-6 and IL-8 were detected in bacteremic patients [31], [34], [35] and further work investigating the cytokine repertoire showed that febrile UTI causes an increase in GRO-α and ENA-78 in urine, and ENA-78 in serum [35]. Acute cystitis has been associated with an increase in urine IL-1α, GRO-α, IL-1β, IL-6, IL-8 and TNF-α compared to sterile samples [36], [37], [38]. Urine cytokine levels in ABU have been examined in transplant patients [39] and diabetic children with ABU [40].…”
Section: Discussionmentioning
confidence: 98%
“…Increased serum levels of IL-6 and IL-8 were detected in bacteremic patients [31], [34], [35] and further work investigating the cytokine repertoire showed that febrile UTI causes an increase in GRO-α and ENA-78 in urine, and ENA-78 in serum [35]. Acute cystitis has been associated with an increase in urine IL-1α, GRO-α, IL-1β, IL-6, IL-8 and TNF-α compared to sterile samples [36], [37], [38]. Urine cytokine levels in ABU have been examined in transplant patients [39] and diabetic children with ABU [40].…”
Section: Discussionmentioning
confidence: 98%
“…Larger studies in future are likely to offer critical insights into the reproducible presence of cytokines in the urine of OAB patients. The bladder source of these cytokines can be confirmed by their comparative detection in plasma or renal urine collected by ureteral catheters [32]. In spite of these differences, the results from this pilot study serve as a framework for a larger, prospective, longitudinal study to investigate the causal relationship of these urinary inflammation biomarkers and symptoms/causes of OAB.…”
Section: Discussionmentioning
confidence: 87%
“…Urinary cytokines in OAB population may reflect the effect of a wide variety of treatments taken by the patients in the study. The obvious advantage of non-invasiveness with urinary proteomics is tempered by the increased variability arising due to intra-individual and inter-individual changes in urine volume, pH, and other urine constituents [31,32]. The approach of creatinine correction for urine levels of biomarkers is routinely used in urine proteomics [33][34][35] and it was considered valid for studies involving measurement of urine chemokines that are believed to be passively released into urine from urothelium during the storage phase of micturition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that UPEC triggers inflammation that consists of immune mediators, including ILs (9)(10)(11)(12), although some of these responses, including, for example, IL-1a, occur in a pathogen-specific manner (13). Roles for TNF, NO (14), CXCR 2 (15), Tamm-Horsfall protein (16,17), and CD44 (18) have been shown in models of human UPEC UTI, although, in most cases, the functions of these host factors at the cellular and molecular levels remain unclear.…”
mentioning
confidence: 99%